The Effect of Perceived Social Support on Recovery Success among Drug Addicts in Rehabilitation Centers in Pakistan - Shaarif, Ammarah; Usman, Benish; Saleem, Adeeba (Annals of Human and Social Sciences, 2025)
The aim of this study was to examine perceived social support's relationship to recovery outcomes (both in terms of frequency of relapse and in the context of ongoing treatment for substance use disorders). In order to survey the recovery, a structured questionnaire was applied to 300 participants from rehabilitation centers in major cities of Pakistan. It was found that perceived social support was highly positively correlated to the recovery success (r = 0.65, p = 0.001) and negatively with the frequency of relapse (r = -0.45, p = 0.01). Results of regression analysis indicated that perceived social support was a significant predictor of recovery success (β = 0.58, p = 0.001) and that gender and level of education also were significant predictors. Recovery success was also found to be gender differentiated, males having a lower recovery success rate than females. It further comes out that recovery success and relapse rates varied with recovery dependent on substance (type) used and the duration of addiction where heroin users fared worst with longer addiction duration being associated with higher relapse frequency. This work gives insight into social support optimized for successful recovery from addiction and rehabilitation strategies improved in Pakistan and other low resource settings.